Women and slavery in the French Antilles, 1635-1848 - Moitt, Bernard (Blacks in the diaspora., 2001)
Women and Slavery in the French Antilles, 1635--1848Bernard MoittExamines the reaction of black women to slavery. In Women and Slavery in the French Antilles, 1635--1848, Bernard Moitt argues that gender had a profound effect on the slave plantation system in the French Antilles. He details and analyzes the social condition of enslaved black women in the plantation societies of Martinique, Guadeloupe, Saint-Domingue (now Haiti), and French Guiana from 1635 to the abolition of slavery in the.